1983
DOI: 10.1161/01.res.52.6.735
|View full text |Cite
|
Sign up to set email alerts
|

The influence of molecular form of local anesthetic-type antiarrhythmic agents on reduction of the maximum upstroke velocity of canine cardiac Purkinje fibers.

Abstract: We studied the local anesthetic effects of the quaternary lidocaine analogues QX-314, QX-572, and QX-222, the tertiary amine lidocaine, its analogues tocainide, 6603, 6211, and the neutral local anesthetic benzocaine to determine if molecular charge of antiarrhythmic agents influences their local anesthetic effects on heart fibers. We used standard microelectrode techniques and canine cardiac Purkinje fibers to compare the effects of stimulation rate, drug concentration, and K+-induced changes in resting membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

1984
1984
1995
1995

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 51 publications
1
23
1
Order By: Relevance
“…However, the present data showed that APD30 was shortened by OPC-88117 at concentrations above 1O-4M. OPC-88117-induced prolongation of APD80 was preserved even when the V,,.x of the action potential, which reflects the sodium channel availability (Gintant et al, 1983;Grant et al, 1984) Hondeghem & Katzung (1977;1980) to explain the interaction between local anaesthetic type (Class I) antiarrhythmic drugs and cardiac sodium channels.…”
Section: Action Potentials Ofpapillary Musclementioning
confidence: 43%
“…However, the present data showed that APD30 was shortened by OPC-88117 at concentrations above 1O-4M. OPC-88117-induced prolongation of APD80 was preserved even when the V,,.x of the action potential, which reflects the sodium channel availability (Gintant et al, 1983;Grant et al, 1984) Hondeghem & Katzung (1977;1980) to explain the interaction between local anaesthetic type (Class I) antiarrhythmic drugs and cardiac sodium channels.…”
Section: Action Potentials Ofpapillary Musclementioning
confidence: 43%
“…Since the entire tissue was excited simultaneously and there was no conduction within the preparation under the present experimental conditions, the decrease in Vmax by Ro 22-9194 or moricizine without any accompanying change in RP reflects an inhibitory effect of these drugs on the fast sodium inward current, INa (Gintant et al, 1983;Grant et al, 1984). The potency of Vmax inhibition by Ro 22-9194 in guinea-pig papillary muscles constantly driven at 1.0 Hz (IC20 = 11 AM) is approximately one tenth of moricizine (IC20 = 1.3 JAM) but is still comparable to those of quinidine, disopyramide or mexiletine (Campbell, 1983).…”
Section: Discussionmentioning
confidence: 83%
“…The characteristics of the use-dependent inhibition of V,,.x induced by pirmenol are similar to those of slow kinetic drugs, such as disopyramide which was shown to have a recovery time constant of 12.0 to 37.8s (Campbell, 1983a;Varro et al, 1985), rather than of fast kinetic drugs, according to the classification proposed by Courtney (1980a). Previous studies indicate that the onset rate of the use-dependent block correlates directly with molecular weight, (Courtney, 1979;1980a,b) and increases with increasing drug concentration (Courtney, 1980a;Gintant et al, 1983;Grant et al, 1984). The studies of 2 ms I I--Onset recovery of Vmax from the block show a strong correlation between molecular weight and recovery times (Courtney, 1980a,b;Grant et al, 1984).…”
Section: Recoveryfrom the Use-dependent Effect Ofpirmenolmentioning
confidence: 80%